2021
DOI: 10.1016/j.jiph.2021.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A patient presenting with ARDS after COVID-19 vaccination: A COVID-19 case report

Abstract: COVID-19 is a disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). The introduction of vaccines against COVID-19 caused great enthusiasm around the world as immunization might end the pandemic. However, it was previously stated that COVID-19 cases would rarely continue to occur despite immunization. Fourteen days after the second dose of the vaccine, a 66-year-old male patient with a negative COVID-19 PCR test result and high levels of IgG and low levels of IgM-A against SARS-CoV-2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Additionally, in a previous study, it was found that participants' primary reasons for being hesitant about receiving the COVID-19 vaccine booster dose were their skepticism regarding the scientific evidence supporting the benefits of the booster dose and the requirement for a booster dose at least once a year, given that it was administered recently [42]. These observations may be associated with earlier case reports [66][67][68][69] which showed a rise in adverse respiratory events among populations with respiratory diseases after COVID-19 vaccination. Nevertheless, emerging evidence suggests that COVID-19 vaccines can be given to patients with COPD or asthma without any safety concerns and with good efficacy [17].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, in a previous study, it was found that participants' primary reasons for being hesitant about receiving the COVID-19 vaccine booster dose were their skepticism regarding the scientific evidence supporting the benefits of the booster dose and the requirement for a booster dose at least once a year, given that it was administered recently [42]. These observations may be associated with earlier case reports [66][67][68][69] which showed a rise in adverse respiratory events among populations with respiratory diseases after COVID-19 vaccination. Nevertheless, emerging evidence suggests that COVID-19 vaccines can be given to patients with COPD or asthma without any safety concerns and with good efficacy [17].…”
Section: Discussionmentioning
confidence: 96%
“…Although severe respiratory adverse reaction after the COVID-19 vaccine is rare, some cases have been reported recently. S. Tutak, et al reported a 66-year-old man with acute respiratory distress syndrome (ARDS) after COVID-19 vaccination and unfortunately, the patient died in ICU [ 16 ]. A 60-year-old patient with Covid-19 vaccine-induced interstitial lung disease (ILD) was reported by Yoshifuji, et al, who indicated COVID-19 vaccine could lead to drug-induced ILD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even when a person is vaccinated, new variants circulating in the community can cause COVID-19. This matter highlights the need to inform the population about the importance of using public health measures that are highly effective, such as wearing masks and engaging in social distancing, even when an individual is already vaccinated [70,71]. Indeed, in the present study, those who considered the vaccine to be the most effective measure to fight the COVID-19 pandemic also said they would increase their social interactions in the short term and would use a mask less often in the presence of their regular contacts, as well as in closed public and open areas.…”
Section: Discussionmentioning
confidence: 99%